When the bloat comes in. (Economist, 1993)
States that as software becomes more sophisticated computers are finding it harder to stomach, and asks if there is an answer to this digital indigestion. Expansion of software programs as each new version is created; The 1990s equivalent of a ten year old word processing program that contained 15,000 lines of computer code now contains at least 500,000 lines; Why not write programs in Assembler (one step up from machine language); Making applications talk to each other; Details.